On-farm performance of genetically improved rohu (Labeo rohita) in Bangladesh: Data - Hamilton, Matthew; Yeasin, Mohammed; Alam, Md. Badrul; Ali, Md. Rayhan; Fakhruddin, Md.; Islam, Md. Mazharul; Barman, Benoy; Shikuku, Kelvin; Shelley, Colin; Rossignoli, Cristiano; Benzie, John (WorldFish, 2023)
Data used for analyses detailed in Hamilton MG, Yeasin M, Alam MB, Ali MR, Fakhruddin M, Islam MM, Barman BK, Shikuku KM, Shelley CC, Rossignoli CM and Benzie JAH (2022) On-farm performance of genetically-improved rohu (Labeo rohita) in Bangladesh. Front. Aquac. 1:1060335. doi: 10.3389/faquc.2022.1060335